ajnpp 2020
DOI: 10.32592/ajnpp.2021.8.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Role of Music Therapy in Reducing the Symptoms of Depression and Anxiety

Abstract: Background: A variety of psychological factors can manipulate the severity of premenstrual syndrome. Objectives: This study aimed to investigate the role of music therapy in reducing anxiety and depression in premenstrual syndrome. Materials and Methods: This quasi-experimental study was conducted based on a pretest-posttest method with a control group. The statistical population of this study included 30 women with the premenstrual syndrome who were referred to Rah-e-Bartar Clinic, Tehran, Iran, in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study relies on music therapy, adopts the methods of music relaxation training and music imagination, and compares the changes of excessive anxiety before and after the implementation, which is found that music therapy also has a relieving effect on test anxiety. However, researchers believe that meditation with guiding words has a guiding and suggestive effect to a large extent and can relieve excessive anxiety [18]. However, it has higher requirements for the meditation environment and varies from person to person and all will go into immersive meditation.…”
Section: Mechanism Of Music Therapy In Intervening Collegementioning
confidence: 99%
“…The study relies on music therapy, adopts the methods of music relaxation training and music imagination, and compares the changes of excessive anxiety before and after the implementation, which is found that music therapy also has a relieving effect on test anxiety. However, researchers believe that meditation with guiding words has a guiding and suggestive effect to a large extent and can relieve excessive anxiety [18]. However, it has higher requirements for the meditation environment and varies from person to person and all will go into immersive meditation.…”
Section: Mechanism Of Music Therapy In Intervening Collegementioning
confidence: 99%